Poetic Fabulations: Chartering Relationalities of Black Flourishing, Mutuality, Inclusive Excellence, and Accountability - Anita Girvan; Maya Seshia; Nisha Nath; Davina Bhandar (Atlantis)
This collective work (four authors) demonstrates how persistent structures in higher education are mobilized in the signing of the Scarborough Charter on Anti-Black Racism and Black Inclusion in Canadian Higher Education: Principles, Actions, and Accountabilities. We read this event against the grain, as an act requiring relation-building and accountability. Recognizing the promises and risks of this work, and inspired by Black Feminist/coalitional practices which disorient from pre-mapped routes and knowledges in universities and reorient to otherwise ways of being, we name this process “poetic fabulation.” We begin with poetry and proceed with seven stanzas that orient thematic reflections in each prose section that follows. The multi-vocality of the piece gives evidence to the experiences of the authors in this work. The interregnum which follows stanza 4, functions at the simultaneous and unruly registers of poetry, analysis, affect, and the somatic, to interrupt the flow, signalling how we experience labouring within the academy. Our work is collaborative, but also entails being hailed and responding in different ways. Using a full spectrum of creative and analytic skills, we navigate towards shared goals to process what we witness in and across post-secondary institution(s), to hold and care for the impacts of discretionary power.